Mengapa Kerja Sama Trilateral Gagal Membendung ISIS: Analisis Teori Kompleks Keamanan Regional - Kumendong, Rachel (Journal of Political Issues, 2026)
This study explains why the Indonesia–Malaysia–Philippines trilateral cooperation has failed to curb regional security threats in the Sulu–Sulawesi Sea. The strategic position of the area has been exploited by ISIS networks to expand their influence and operations across Southeast Asia, intensifying security challenges in the tri-border region. In response, the three states established trilateral cooperation as a mechanism to suppress ISIS’s activities. However, empirical developments show that ISIS operations continued to grow despite this initiative. Guided by the Regional Security Complex Theory (RSCT) and using a deductive qualitative method, the findings reveal three interconnected factors that explain the TCA’s failure to curb ISIS expansion between 2017–2019. First, the geographical proximity and porous maritime borders of the Sulu–Sulawesi Sea facilitated the movement of foreign terrorist fighters, weapons, and financial flows, creating shared vulnerabilities that were not jointly managed. Second, interstate distrust, sovereignty sensitivities, and divergent threat perceptions hindered the institutionalization of coordinated mechanisms such as Joint Maritime Patrols, preventing cohesive operations. Third, limited and asymmetrical external involvement—particularly from the United States—focused on technical support rather than addressing root causes, weakening regional autonomy and coherence.